Assessment of the Impact of Adjunctive Proactive Telephone Counseling to Promote Smoking Cessation among Lung Cancer Patients' Social Networks. Issue 3 (January 2013) - Bastian, Lori A.; Fish, Laura J.; Peterson, Bercedis L.; Biddle, Andrea K.; Garst, Jennifer; Lyna, Pauline; Molner, Stephanie; Bepler, Gerold; Kelley, Mike; Keefe, Francis J.; McBride, Colleen M.
Purpose: When a patient is diagnosed with lung cancer, members of his/her social network may be more likely to engage in smoking cessation efforts. Proactive telephone counseling combined with a tailored self-directed intervention may be more effective at promoting smoking cessation than a tailored self-directed intervention alone. Design: Randomized controlled trial. Setting: Four clinical sites. Subjects: Current smokers who are family members and close friends of patients with lung cancer. Intervention: Six counselor-initiated counseling calls using motivational interviewing techniques and focusing on teaching adaptive coping skills based on the transactional model of stress and coping along with tailored self-directed materials (including nicotine patches, if not contraindicated) (n = 245) vs. tailored self-directed materials (including nicotine patches, if not contraindicated) (n = 251). Measures: Participants were surveyed at baseline and at 2 weeks, 6 months, and 12 months postintervention. The outcome was 7-day point prevalent abstinence. Analysis: The objective of this study was to test for arm differences in smoking cessation rates at 2 weeks and 6 months postintervention (primary) and at 12 months postintervention (secondary). Results: We found no overall effect of the proactive intervention on cessation rates. Among younger participants (age <50), the cessation rate in the intervention group was higher than in the control group at 2 weeks postintervention (16% vs. 4%, p = .046). For older participants (age >50), there were no group differences. Conclusion: Proactive telephone counseling focusing on adaptive coping skills was difficult to implement among smokers in lung cancer patients' social network. Although this study did not demonstrate any added benefit to cessation rates, this null finding may be a result of an intervention that was weaker than intended, owing to difficulties in completing the counseling phone calls. We discuss lessons learned and areas for future research in this special population.